Drosófilas associadas a fruto de parahancornia amapa dispersos sobre o solo da floresta-padrão de oviposição. - Costa, Edilene Góes da (Museu Paraense Emílio Goeldi, 2022)
This paper aims to describe the life-long oviposition patterns of females of 5 Drosophila species whose lineages originated from individuals emerging from Parahancornia amapa fruit Drosophila paulistorum, D. willistoni, D. malerkotliana, D. sturtevanti, O tropicalis. Fl females from the crossing of two laboratory-grown strains were used. Between 15 and 25 pairs of each species were individualized in boxes containing oviposition medium, distributed in a small, removable petri dish. The plates were changed daily, and the eggs counted. At each change, the plate with medium was brushed with 8% biological yeast (Saccharomyees eerevisae). Egg counting stopped with the death of the female, without replacing the dead males. D paulistorum started oviposition at 3 days, reaching its peak at 10 days: with 40 eggs laid per female/day. After that, the number of eggs declined evenly, about 10 eggs per day, and ceased with the death of the females at 60 days. D willistoni started ovipositing at 3 days. Peak oviposition occurred between day 5 and 15 with females producing around 35 eggs per day. After this period egg production oscillated around 20 eggs per day, until the death of the last female at 89 days. D. tropiealis oviposited from 2 days of age, presenting between the 3rd and 30th day, modal values between 30 and 35 eggs per female. After this period, oviposition extended for a little over a month, with an average daily production of 14 eggs/female. D. sturtevanti started oviposition at 4 days. The number of eggs per female per day reached a picc between 35 and 45 days of age with 20 eggs. After 45 days, the number of eggs declined, ceasing oviposition with the death of the females at 86 days. The females of D. malerkotliana started oviposition at less than 48 hours of age, reaching their maximum capacity between 3 and 15 days of age (35 eggs/female/day) decreasing exponentially until the 80 days of life of the females These data show that the species differ in terms of oviposition strategy. D. malerkotliana has the most concentrated reproduction in the early life period while D sturtevanti is the later, with the species of the willistoni subgroup in an intermediate position.